Agrifood value chains: Building resilient food systems - Minten, Bart; Belton, Ben; Reardon, Thomas (International Food Policy Research Institute, 2023)
Agrifood value chains in the world’s low- and middle-income countries (LMICs) have expanded rapidly over the past decade, supplying an increasing volume and diversity of food products. This transformation has been driven by the fast growth of urban and peri-urban areas as well as increasing demand from richer and more urban consumers for different, higher-quality, and often more expensive food. More farmers than ever are now connected to agrifood value chains through markets for both agricultural inputs and outputs. These connections are not only ncreasingly numerous but also increasingly complex, reflecting the greater diversity of products, inputs, and services that farmers buy and sell. Midstream and downstream in agrifood value chains, a “quiet” revolution has occurred in logistics, storage, transport, wholesale, retail, and food services, with fundamental and rapid changes in the structure, conduct, and performance of these value chain segments and the enterprises involved.